The problem of environmental awareness in terms of the eco-innovation implementation in enterprises - Joanna Machnik-Słomka; Iwona Kłosok-Bazan (Economic and Environmental Studies (E&ES), 2017)
Environmental awareness of managers and employees can be an important factor favouring the implementation of eco-innovation in enterprises. This article aims to identify the role of entrepreneur's ecological awareness in implementing the eco-innovation. In order to attain this purpose, the literature analysis in the field of environmental awareness and eco-innovation was conducted. The results of this analysis were the basis for the design and performance of the in-depth qualitative research based on a case study of a selected enterprise. As shown in the presented example, the high level of environmental awareness of entrepreneur translates into the company value systems and, additionally, it shapes the right attitude and pro-ecological preservation.
Keywords: Q01; Q5; L31; 330; environmental awareness; eco-innovation; sustainable development